Serial assessment of early antibody binding to decellularized valved allografts - Oripov, Firdavs; Ramm, Robert; Falk, Christine; Goecke, Tobias; Ebken, Johannes; Jashari, Ramadan; Böthig, Dietmar; Horke, Alexander; Avsar, Murat; Bobylev, Dmitry; Haverich, Axel; Hilfiker, Andres; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives Decellularized homograft valves (DHV) appear to elicit an immune response despite efficient donor cell removal. Materials and methods A semiquantitative Dot-Blot analysis for preformed and new recipient antibodies was carried out in 20 patients following DHV implantation on days 0, 1, 7, and 28 using secondary antihuman antibodies. Immune reactions were tested against the implanted DHV as well as against the stored samples of 5 non-implanted decellularized aortic (DAH) and 6 pulmonary homografts (DPH). Results In this study, 20 patients (3 female and 17 male patients) were prospectively included, with a median age of 18 years and an IQR of 12–30 years. Six patients received DPH and 14 received DAH. The amount of antibody binding, averaged for all patients, decreased on post-operative days 1 and 7 compared to pre-operative values; and on day 28, antibody binding reached close to pre-operative levels (16.8 ± 2.5 on day 0, 3.7 ± 1.9 on day 1, 2.3 ± 2.7 on day 7, and 13.2 ± 3.7 on day 28). In comparison with the results in healthy controls, there was a higher amount of antibody binding to DAH than to DPH. The mean number of arbitrary units was 18.4 ± 3.1 in aortic and 12.9 ± 4.5 in pulmonary DHV (p = 0.140). Male patients exhibited higher antibody binding to aortic DHV than female patients (19.5 ± 2.1 vs. 1.6 ± 6.7). The p-value calculation was limited, as only two female patients received DAH. There was no correlation between the amount of overall antibody binding to DHV with respect to donor age (Kruskal–Wallis test p = 0.550). DHV recipients with a sex mismatch to the donor showed significantly less antibody binding (6.5 ± 1.8 vs. 13.7 ± 1.8; p = 0.003). Our main finding was an increase in antibody binding in younger patients receiving decellularized aortic allografts. This increase was higher in patients with early degeneration signs but was not specific to the individual DHV implanted nor previous DHV implantation. Antibody binding toward explanted DHV was significantly increased in implicating antibody-mediated DHV degeneration. Conclusion Serial assessment of tissue-specific antibody binding revealed an increase in some patients within 4 weeks after surgery, who subsequently developed early signs of allograft degeneration. Further studies with larger sample sizes are needed to confirm the prognostic relevance of increased antibody activity in addition to targeted research efforts to identify the molecular agents triggering this type of antibody response.